Dampak PSAK 73 terhadap Kualitas Laba Sektor Jasa dan Sektor Konsumsi BEI 2024: Analisis Komparatif ROA dan NPM - Neng Entang Fatimah Iam Nur; Corie Armani; Lendra Yenti; Elzhariyanti Elzhariyanti; Nofryanti Nofryanti (Lembaga Pengembangan Kinerja Dosen, 2025)
The implementation of PSAK 73 requires the recognition of right-of-use assets (ROU) and lease liabilities (LL) on the balance sheet, along with depreciation and interest expenses (DIE) in the profit and loss statement, aimed at improving financial transparency. This study analyzes the impact of PSAK 73 on earnings quality in the services and consumer sectors listed on the Indonesia Stock Exchange (IDX) during the 2024 period. The primary focus is on the indicators Return on Assets (ROA) and Net Profit Margin (NPM). The research uses a descriptive comparative method with tables and graphs to analyze ROU, LL, DIE, ROA, and NPM. The findings show that the consumer sector is more dependent on leased assets, with significantly higher values of ROU, LL, and DIE compared to the services sector. This could potentially pressure ROA due to higher depreciation, though the consumer sector enjoys a better NPM due to larger scale operations and quicker cash turnover. Conversely, the services sector shows more stability but is volatile due to higher operational costs. This study emphasizes the importance of efficiently managing lease assets to maintain profitability and encourages future research with larger samples and long-term trend analysis to further understand the impact of PSAK 73.